WAVEWATCH III: Transition to Naval Operations - Dykes, James D; Rogers, W E (2011)
Knowledge of the sea state and ocean wave conditions is important for Naval operations, and it calls for real-time operational support of wave forecasts. Two operational centers have been providing such support. The Fleet Numerical Meteorology and Oceanography Center (FNMOC) in Monterey, California, produces and delivers wave forecasts covering large spatial and long time scales to support general operations. The Naval Oceanographic Office (NAVOCEANO) at Stennis Space Center, Mississippi, provides small-scale wave forecasts covering shorter intervals to support specific missions involving littoral waters and surf zones. The Naval Research Laboratory (NRL) at Stennis Space Center has been the primary transition partner with NAVOCEANO for enabling technologies in wave forecasting for small and intermediate scales. And, in cooperation with the National Centers for Environment Prediction, the larger scale WAVEWATCH III model in its current state has been transitioned to FNMOC with a newer version coming to both NAVOCEANO and FNMOC within this year. To provide wave energy boundary conditions to smaller scale wave models such as SWAN (Simulating Waves Nearshore), NAVOCEANO runs the WAM (WAve Model) for a set of large-scale domains around the world. Replacing the WAM, NRL is developing and testing a system that will implement the multi-grid model version of WAVEWATCH III at NAVOCEANO. In addition, NRL is providing upgrades to the system at FNMOC to include curvilinear gridded domains, particularly to cover the Arctic Ocean. Comparisons of WAM and WAVEWATCH III were made with in situ observations and altimeter measurements. The multi-grid system will be an improvement to the current wave modeling systems in place at NAVOCEANO and FNMOC, because the new configuration will save processing time and promises to increase forecast accuracy. Preliminary validation results seem to bear this out. Presented at the Ocean Waves Workshop held at the University of New Orleans, Louisiana, on 17 November, 2011.